1974
DOI: 10.1029/ja079i010p01527
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the quenching of vibrationally excited nitrogen by atomic oxygen

Abstract: A photo-ionization detector for vibrationally excited nitrogen (N2*) has been used to obtain the rate of quenching of N2* by atomic oxygen in the temperature range 300ø-723 øK. The quenching rate coefficient was found to be 3.2 X 10 -•5 cm 3 s -• at 300øK, 1.3 X 10 -•4 cm 3 s -• at 463øK, 2.7 X 10 -•4 cm a s -• at 633øK, and 4.0 X 10 -• cm a s -• at 723øK. These rate coefficients are extremely large compared with the expected values for a conventional vibrational-translational (VT) energy transfer process in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The contributions of suprathermal electrons via electronic triplet states and of transport processes are neglected. At altitudes ≥300 km the main quencher of vibrational states is atomic oxygen with the rate coefficient [ McNeal et al , 1974] L O ≃ 10 −10 · exp(−70/ T n 1/3 ) · [ O ] s −1 ([ O ] represents the atomic oxygen density). Accounting for charge transfer yields L V = L O + c V · k 1,0 · n i s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of suprathermal electrons via electronic triplet states and of transport processes are neglected. At altitudes ≥300 km the main quencher of vibrational states is atomic oxygen with the rate coefficient [ McNeal et al , 1974] L O ≃ 10 −10 · exp(−70/ T n 1/3 ) · [ O ] s −1 ([ O ] represents the atomic oxygen density). Accounting for charge transfer yields L V = L O + c V · k 1,0 · n i s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The main quencher of the N 2 vibrational excitation in the ionosphere is atomic oxygen. The rate coefficient of this V‐T process is given by the formula [ McNeal et al , 1974]: …”
Section: Main Features Of Vibrational Kinetics In the F Region Duringmentioning
confidence: 99%
“…Waite et al [1979] reexamined the vibrational equilibrium temperature in aurorae and concluded that efficient quenching by O [McNeal et al, 1974] makes it unlikely that N 2 vibrational temperatures are high enough to permit entrapment. ating on higher vibrational levels (v" = 1, 2 .... ) of the ground state or that there is enough vibrationally excited N 2 in the thermosphere to make even those bands optically thick.…”
Section: Recent Observations Of the Far And Extreme Ultraviolet Spectmentioning
confidence: 99%